The Relationship between Smoking History with ECOG Score, EGFR Mutation Status, and Clinicopathology Data of NSCLC Patients: Preliminary Study - Jayadi, Tejo; Amarantini, Charis; Saputra, Lili Ananta; Pratiwi, Johana Puspasari Dwi; Widowati, Fransiska Galuh (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2026)
Background: Patients with non-small cell lung cancer (NSCLC) have a poor outcome. Mutations in the EGFR gene play a crucial role in determining treatment options and prognosis. Smoking history, clinicopathological features, including patient performance, and EGFR gene mutation have served as clinical guidelines for monitoring. This study aims to examine the association between smoking history and ECOG score, EGFR mutation status, and clinicopathological characteristics of patients with NSCLC in Yogyakarta. Methods: An observational and analytic study, with a retrospective cohort design from 32 patients diagnosed with NSCLC. Data on smoking history, clinicopathological characteristics, ECOG performance scores, and EGFR mutation types (Exon 19 deletion and Exon 21 L858R) were extracted and concluded from medical records. The relationship between these variables was analysed using the Chi-square test. Results: The analysis began by exploring the relationship between smoking history and initial ECOG performance scores. It was discovered that non-smokers exhibited poorer initial ECOG scores (P=0.025). Smoking history was significantly associated with specific EGFR mutation types (P=0.009), but not with overall EGFR mutation status. The analysis revealed that deletions on Exon 19 were mainly found in patients who smoked, whereas mutations in Exon 21 were uniquely present in non-smokers. Clinical follow-up also shows an association (P=0.002). This finding suggests that smoking behaviour interferes with the carcinogenesis of NSCLC. Conclusion: The relationship between smoking history, performance status, exon-specific EGFR mutations, and clinical follow-up suggests differences in the carcinogenic mechanisms of NSCLC exon-specific mutations, highlighting biological diversity and emphasizing the need for detailed molecular studies to improve prognostic accuracy.